Blood pressure monitoring during exercise: Comparison of pulse transit time and volume clamp methods. (2nd November 2015) - Wibmer, Thomas; Denner, Coy; Fischer, Christoph; Schildge, Benedikt; Rüdiger, Stefan; Kropf-Sanchen, Cornelia; Rottbauer, Wolfgang; Schumann, Christian
Abstract : During physical exercise, pulse transit time (PTT), expressed as the interval between ventricular electrical activity and peripheral pulse wave, may provide a surrogate estimate for blood pressure by the use of specific calibration procedures. The objective of this study was to determine systolic blood pressure (SBP) values derived from the PTT method and from an established method of non-invasive continuous blood pressure measurement based on the volume clamp technique, and to compare their agreement with sphygmomanometry during exercise tests. In 18 subjects, electrocardiogram (ECG) and finger-photoplethysmography were continuously recorded during maximal cycle exercise tests. Intermittent and continuous blood pressure measurements were simultaneously taken using automated sphygmomanometry and a Portapres Model-2 device, respectively. PTT was calculated for each ECG R-wave and the corresponding steepest upstroke slope in the photoplethysmogram, and was transformed to a continuous blood pressure estimate using multipoint nonlinear regression calibration based on the individual subject's sphygmomanometer readings. Bland–Altman limits of agreement between PTT-derived SBP estimates and sphygmomanometer values were –24.7 to 24.1 mmHg, and between Portapres and sphygmomanometer SBP values were –42.0 to 70.1 mmHg. For beat-to-beat SBP estimation during exercise, PTT measurement combined with multipoint nonlinear regression calibration based on intermittent sphygmomanometry may be an alternative to volume clamp devices.